1995
DOI: 10.1073/pnas.92.14.6464
|View full text |Cite
|
Sign up to set email alerts
|

An A-DNA triplet code: thermodynamic rules for predicting A- and B-DNA.

Abstract: The ability to predict macromolecular conformations from sequence and thermodynamic principles has long been coveted but generally has not been achieved. We show that differences in the hydration of DNA surfaces can be used to distinguish between sequences that form A-and B-DNA. From this, a "triplet code" ofA-DNA propensities was derived as energetic rules for predicting A-DNA formation. This code correctly predicted >90% of A-and B-DNA sequences in crystals and correlates with A-DNA formation in solution. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 39 publications
3
65
0
1
Order By: Relevance
“…2). When applying previous trinucleotide rules to distinguish A-DNA from B-DNA, those derived from calculations of hydrophobic surfaces (14) correctly predicted 16͞24 (67%) of the sequences crystallized as A-or B-DNA, whereas those from experimental alcohol titrations (13) correctly predicted 21͞28 (75%) sequences (not all trinucleotides are represented in the respective scales). The relatively poor showings reflect the fundamental differences between these two CCnnnN6N7N8GG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). When applying previous trinucleotide rules to distinguish A-DNA from B-DNA, those derived from calculations of hydrophobic surfaces (14) correctly predicted 16͞24 (67%) of the sequences crystallized as A-or B-DNA, whereas those from experimental alcohol titrations (13) correctly predicted 21͞28 (75%) sequences (not all trinucleotides are represented in the respective scales). The relatively poor showings reflect the fundamental differences between these two CCnnnN6N7N8GG).…”
Section: Discussionmentioning
confidence: 99%
“…This IR sequence motif also has the potential to adopt other DNA structures; the trinucleotide has been suggested to be the minimum motif to distinguish between the double-helical forms of B-and A-DNA (13,14). Thus, we expected the current crystallographic screen to sample at least three different DNA structures (Fig.…”
mentioning
confidence: 99%
“…A-form DNA Predictive Methods-A-DNA propensity energy values for the duplex oligonucleotides were calculated using the method of Basham et al (38). The method was modified to determine the percentage of each duplex in either A-or B-form using the following classifications and rules.…”
Section: Methodsmentioning
confidence: 99%
“…Because dsRBDs may be expected to have a preference for binding A-form structure, we initially used the method of Basham et al (38) to calculate the average A-DNA forming potential for each of the oligonucleotides used in this study (Table III). We refined this method to predict the percentage Aand B-forms for each duplex (see "Experimental Procedures"); this is shown as "predicted" in Table III.…”
Section: Mutations In the Dsrbds Of Cbtf 122 En Lead To A Loss Ofmentioning
confidence: 99%
“…For unmodified mica in pH 7 solution, this charge is~0.003 C/m 2 (20), corresponding to~1 M ion concentration at the surface (5). Hydration effects are entropy driven, so the effect of the relative hydrophobicity of the surface environment will be enhanced at lower temperature, increasing the driving force for a B to A transition (21). We also studied the supercoiled plasmid pUC19, but found that almost all of the DNA collapsed on cooling into a form that did not permit measurement of contour lengths.…”
Section: Resultsmentioning
confidence: 99%